2022
DOI: 10.1016/j.idcr.2021.e01354
|View full text |Cite
|
Sign up to set email alerts
|

A case of sepsis due to a rare carbapenem-resistant Ignatzschineria species

Abstract: Ignatzschineria species have emerged only recently and few cases have been identified worldwide. It has been determined that maggots likely serve as the vector of transmission and the majority of cases described involved cutaneous myiasis. This article presents the first case of an Ignatzschineria species closely related to I. larvae/I. ureclastica causing bacteremia in North America. This isolated Ignatzschineria species is also u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…These results indicated that the addition of illite in the composting process effectively inhibited the growth and survival of Streptococcus (with low relative abundance <0.01%) in the mature compost. These results were consistent with those previously reported ( Coelho et al, 2022 ; Maniam and Argentine, 2022 ). Fermentimonas was revealed with the highest relative abundance at the end of the composting process, which was probably associated with the degradation of glucose and fructose and involved in heavy metal passivation, showing the highest relative abundance at the end of composting of group I-5.…”
Section: Resultssupporting
confidence: 94%
“…These results indicated that the addition of illite in the composting process effectively inhibited the growth and survival of Streptococcus (with low relative abundance <0.01%) in the mature compost. These results were consistent with those previously reported ( Coelho et al, 2022 ; Maniam and Argentine, 2022 ). Fermentimonas was revealed with the highest relative abundance at the end of the composting process, which was probably associated with the degradation of glucose and fructose and involved in heavy metal passivation, showing the highest relative abundance at the end of composting of group I-5.…”
Section: Resultssupporting
confidence: 94%
“…There are three genera of Ignatzschineria: larvae , indica , and ureiclastica . All three genera are non-sporulating, non-haemolytic, non-motile, rod-shaped bacteria that were first isolated in 2001 from larvae of Wohlfahrtia magnifica, a parasitic flesh fly causing myiasis in several animal species and occasionally in humans [ 4 ]. Originally the name of this bacterium was simply Schineria in honour of Ignatz Rudolph Schiner (1813-1873), who first described the fly Wohlfahrtia magnifica in 1862 [ 3 ].…”
Section: Discussionmentioning
confidence: 99%